Traditional Heritage Boat Surveys : Grand Canal, Royal Canal, Barrow Navigation 2016 : Shannon Navigation and Shannon-Erne System 2017 : an initiative of the Waterways Ireland Heritage Plan 2016-2020.: Grand Canal, Royal Canal, Barrow Navigation 2016 : Shannon Navigation and Shannon-Erne System 2017 : an initiative of the Waterways Ireland Heritage Plan 2016-2020. ([2017]) - Waterways Ireland,; Heritage Boat Association,; Inland Waterways Association of Ireland,; Meitheal Mara (Community boatyard),
No abstract available